Development Of Artistic Digital Quranic Interpretation Toward Innovative Foreign Language Learning - Madjid Muh. Naim; Basalamah Salah (SHS Web of Conferences)
This research attempts to develop a model of artistic quranic digital interpretation toward innovative foreign language learning to increase student’s insight on quranic understanding. The purpose of research is to introduce alTashwir alFanniy (TF) model and the student’s opinions about the TF. This quranic interpretation will use several digital exegesis books and non-digital to highlight deeply selected quranic verses. Descriptive analysis approach was used in this qualitative research to take a generalization of the quranic digital interpretation that the selection of controlled samples will produce a reliable answer. The data of population were collected by using the Simple Random Sampling (SRS) and the questionnaire used Lickert scale by twenty of selected respondents. The most important results is there is 70% respondents agreed that alTashwir alFanniy (TF) in the quranic interpretation is very interesting to be learned, 85% respondents agreed that alTahswir alFanniy based on 4 C’s of 21st century skills is easy to be understood and applied in obtaining new insights and deep contemplation in this digital era, and 75% respondents agreed that students can improve their Arabic and English vocabularies by using alTashwir alFanniy model based on technology application.